Dressing in white, a true brazilian tradition: social influence, values, and symbolic consumption - Melo, Francisco Vicente Sales; Farias, Salomão Alencar de; Barbosa, Ohana Trajano (Revista de Administração da UFSM, 2019)
This article seeks to understand how the individual interpretation of the social influence of groups and personal values relate to the symbolic consumption of white clothes in the festivities of New Year’s Eve, a true Brazilian tradition. For that, we used a descriptive research design with personal interviews and survey, using thematic analysis and logistic regression. The results indicated that if it is necessary to be part of a group, people who value warm relations with others, fun and enjoyment, and who can modify their social self-presentation, are more likely to wear white clothes in this time of the year. Also, as for personal values, it was verified that if the use of white clothes favors the warm relations with others, fun, and enjoyment, there will be a high probability that one will wear white in the turn of the year. Our contribution relies on studying a typical Brazilian tradition that has an impact on apparel retailing sales and needs a better academic understanding. In terms of management, there is a clear indication of the social consumption of the clothes, and of group influence, which can be used in communications arguments from retailers to consumers.